Small and Medium-Sized Firms' Strategies and Export Performance: An Empirical Study - Gentzoglanis, Anastassios (CIENCIA ergo-sum, 2017)
The present paper is an empirical study of innovation and export performance of small and medium-sized firms. By separating a sample of small and medium-sized manufacturing firms in Canada into two categories, high and low exporter; and by assigning each of them their corresponding innovativeness index, we relate the firms' technological characteristic to their export involvement. The results do not reject the hypothesis ones in the export markets.